Outsourcing of archival documentary management: a mapping in the metropolitan region of Florianópolis-SC - Gonçalves, Rodrigo Marcelo (2018)
This study aims to map the archival services contracted by public and private institutions and the services provided by companies that outsource Archival Document Management in the Metropolitan Region of Florianópolis (SC). Concepts related to document management, archival functions, user and outsourcing are discussed. From the methodological procedures to reach the objectives of the study, the type of exploratory research was used, to approach the problem, the qualitative and the quantitative research. Through web searches, the companies that provide archival services and companies that purchase customers were identified. To map the outsourced services, two questionnaires were applied: one for companies providing archival services and another for client companies. Finally, it was estimated the satisfaction of the client companies regarding the outsourcing of management in their archives. Out of the results referring to the companies providing the services, it is noted that the services most hired / sought are organization, digitization and document storage in conventional means. Information on the frequency of request of the documents, procedures for sending / delivering the document and an estimate of the time it takes to be sent is also indicated on the chart. As for the client companies, it is noted that they are satisfied with the outsourced archival services received. It is concluded that the topic addressed in the study is scarce in Archivology, but, nevertheless, it was possible to reach the objectives proposed in this study.